Letters of bank guarantee, photocopies and the difference between them and the bank guarantee. Juristic study - مغديد كريم طه (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Banking guarantees are of great importance in the growth of economic life and the development of business processes. They are a means of facilitating and need financing when an obligation falls on a party to provide money, service or goods to the other party, as well as in cases where a liability may arise, And that the application of the letter of guarantee is not confined to the local domain but rather originated primarily in international transactions, and that the letter of guarantee varies P Because the guarantee creates an original obligation on the bank guarantor, which is the independence of the debt secured from the original obligation, and that the fees obtained by the Islamic banks in return for the issuance of letters of guarantee are a commission due to them for the administrative expenses and banking services provided to their clients professionally.